Evaluasi Pemeliharaan Taman Gelanggang Olahraga Ngurah Rai Denpasar, Bali - Amerta, I Putu Wahyu; Pradnyawathi, Ni Luh Made; Sukewijaya, I Made (Nandur, 2023)
The Ngurah Rai Sports Center (GOR) has many facilities as well as a park for sports and recreations. Not only used for sports, GOR Ngurah Rai is also used for art events and other events. In supporting these activities, it is necessary to pay attention for the maintenance issues as a follow-up activity. Insufficient manpower in maintaining GOR can affect the level of efficiency and effectiveness of work capacity, so this study aims to provide recommendations regarding good maintenance standards so that users are safer and more comfortable in their activities at the Ngurah Rai GOR. This study used observation, interviews, questionnaires and literature studies, focusing on visitor perceptions and maintenance of the park at GOR Ngurah Rai. The type of research is descriptive quantitative with weighting analysis using a Likert scale. This research is based on the perceptions of respondents and the results obtained from the aspects of cleanliness, safety, maintenance, and beauty with an average value of 61.45% so are categorized as good. While the results of interviews with the Office of Education, Youth and Sports as the manager of GOR Ngurah Rai, it is known that the maintenance and management of GOR Ngurah Rai do not have good maintenance standards. Therefore, it is necessary to have recommendations for maintenance standards of GOR Ngurah Rai in order to create good maintenance. Suggestions that can be given are the preparation of standard operating procedures related to the implementation of park maintenance, adding field supervisors, adding and repairing work tools to support the maintenance of GOR Ngurah Rai for the better results.